PERAN NOTARIS DALAM PENYULUHAN HUKUM SEHUBUNGAN DENGAN AKTA PERJANJIAN PENGIKATAN JUAL BELI (PPJB) STATUS OBJEK TANAH NEGARA DAN MENGAKIBATKAN KERUGIAN MATERIIL BAGI PEMBELI - Sholiha, Mar Atus (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
In providing services to the community there are two important things, namely the making of authentic deeds including the PPJB deed relating to the trade of state land, and providing legal counseling to the public. Legal consouling by Notary must be did for and for legal actions did by notaries at the request of their clients. In the case of taking legal action for his client, the notary may also not side with his client, Notary must be neutral, because the task of the notary is to prevent the occurrence of problems. This normative juridical research uses a statute approach and conceptual approach. This research is limited to the discussion forms of legal protection the object buyers of State land through the Deed Agreement of Trade Binding (PPJB) which is not given legal counseling by Notaries, and Notary responsibilities in connection with the PPJB Deed with the object of state land before a Notary are not preceded by legal counseling of parties in relation to land status. The results from this study explain that in the PPJB deed there is a legal relationship between the legal subject and objects which creates the rights and obligations that also need to get legal protection. Forms of legal protection against buyers of State land object through the Deed Agreement of Trade Binding (PPJB) made by a  Notary that trade object is state land and cannot be traded with the status of property rights is by Submit a claim for cancellation of the deed and Submit a claim for compensation to both the seller and the Notary. The notary is responsible in connection with the Deed Agreement of Trade Binding (PPJB) with the object of state land made before a Notary whose services are not preceded by legal counseling because there is a legal relationship between the Notary with the respondent, but not contractual relations.